Three Distinct Amine Receptors Operating at Different Levels within the Locomotory Circuit Are Each Essential for the Serotonergic Modulation of Chemosensation in Caenorhabditis elegans - Harris, Gareth P. (Society for Neuroscience, 2009)
Serotonin modulates behavioral plasticity in both vertebrates and invertebrates and in Caenorhabditis elegans regulates key behaviors, including locomotion, aversive learning and olfaction through at least four different 5-HT receptors. In the present study, we examined the serotonergic stimulation of aversive responses to dilute octanol in animals containing null alleles of these 5-HT receptors. Both ser-1 and mod-1 null animals failed to increase sensitivity to dilute octanol on food/5-HT, in contrast to wild-type, ser-4 or ser-7 null animals. 5-HT sensitivity was restored by the expression of MOD-1 and SER-1 in the AIB or potentially the AIY, and RIA interneurons of mod-1 and ser-1 null animals, respectively. Because none of these 5-HT receptors appear to be expressed in the ASH sensory neurons mediating octanol sensitivity, we identified a 5-HT(6)-like receptor, F16D3.7(SER-5), that was required for food/5-HT-dependent increases in octanol sensitivity. ser-5 null animals failed to increase octanol sensitivity in the presence of food/5-HT and sensitivity could be restored by expression of SER-5 in the ASHs. Similarly, the RNAi knockdown of ser-5 expression in the ASHs of wild-type animals also abolished 5-HT-dependent increases in octanol sensitivity, suggesting that SER-5 modulates the octanol responsiveness of the ASHs directly. Together, these results suggest that multiple amine receptors, functioning at different levels within the locomotory circuit, are each essential for the serotonergic modulation of ASH-mediated aversive responses.